Exploring the Equality of Urban Community Greening: A Case Study of Guangzhou, China - Liu, Yujie; Yu, Potong (International Journal of Natural Resources and Environmental Studies, 2025)
This study focused on the Urban Heat Island (UHI) effect especially in Guangzhou, China. The UHI effect happens when urban areas trap more heat than their natural counterparts. Through field air temperature measurements of multiple areas with high and low tree canopy cover areas, this study strongly suggested the existence of the UHI effect in Guangzhou; it showed that areas with low tree canopy cover had a significant higher air temperature than areas with greater tree canopy cover. Another area of focus for this study is the correlation between greening rates in residential villages in Guangzhou, China, and apartment price per square meter. The study gathered numerous datapoints of residential villages Guangzhou and found that there was a moderate positive correlation. These factors warrant the necessary and timely incorporation of more greenspaces in the urban landscape.